1999
DOI: 10.1007/s11746-999-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot‐plant fractionation of soybean glycinin and β‐conglycinin

Abstract: A laboratory process for separating glycinin and β-conglycinin from soybean flakes was successfully scaled up to the pilot-plant scale (15 kg soy flakes). Average yields of the glycinin and β-conglycinin fractions were both 9.4% on a dry basis (db). The protein contents of glycinin and β-conglycinin fractions were 92.8 and 97.7% db, respectively. The glycinin and β-conglycinin purities were 90.4 and 72.7% of the protein content, respectively, which were very comparable to those of the laboratory-scale process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 18 publications
13
101
5
Order By: Relevance
“…Glycinin fraction weight was lower at 65°C. These data support the hypothesis of Wu et al (10) that the intermediate fraction is primarily composed of glycinin and -conglycinin proteins that are no longer in their native state. The whey fraction weights were not different, indicating that denatured protein was not being partitioned into whey.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Glycinin fraction weight was lower at 65°C. These data support the hypothesis of Wu et al (10) that the intermediate fraction is primarily composed of glycinin and -conglycinin proteins that are no longer in their native state. The whey fraction weights were not different, indicating that denatured protein was not being partitioned into whey.…”
Section: Resultssupporting
confidence: 91%
“…Wu et al (10) indicated that most of the glycinin and -conglycinin proteins comprising the intermediate fraction were no longer in the native state. It is probable that as the native state was lost and due to protein unfolding, more hydrophobic areas were exposed to interact with the isoflavones.…”
Section: Resultsmentioning
confidence: 99%
“…Surface hydrophobicity was measured by using the methods of Wu et al (9) with 1-anilino-8-naphthalene sulfonic acid magnesium salt monohydrate (ANS; ICN Biomedicals, Inc., Aurora, OH). Protein dispersions (prepared as in the solubility test) were stirred, adjusted to pH 7.0, and centrifuged at 10,000 × g and 20°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The soy protein fractionation procedure utilized as the control in the present study has been reported by Wu et al [17] and was a modification of a procedure first reported by Nagano et al [18]. About 100 g of defatted soy flour was extracted with de-ionized water at 15:1 water-to-flour ratio, the pH was adjusted to 8.5 with 2N NaOH, and the resulting slurry was stirred for 1 h. After centrifuging at 14,300·g and 15°C for 30 min, the protein extract (1st extract) was decanted, and the amount of insoluble fiberrich residue was determined and sampled for proximate composition.…”
Section: Preparation Of Spimentioning
confidence: 99%